Phenol test and electrophoresis of seed esterases for testing genetic purity in seed lots of pearl milllet (Pennisetum glaucum) inbreds - Varier, Anuradha; Dadlani, Malavika; Sharma, S P (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during 1993 to explore possibility of using phenol test and electrophoresis of seed esterases fortesting the genetic purity of seed lots or pearl millet [Pennisetum glaucume (L.) Br. emend. Stuntz.] inbreds. Ten inbredlines of pearlmillet (ICMB 87001', 'ICMB 87003', 'ICMB 88004', 'ICMB 88006', 'ICMB 89111', 'ICMB 90111', '841 B', '81 B','843 B' and '5141 B') could be grouped into 4 different colour categories using phenol test. Contamination of a seed lot onlywith seed of a different colour category could be detected by this technique. Polyacrylamide gel electrophoresis of seedesterases could differentiate each of these lines individually. This test could detect an artificial contamination of 4% (2seeds of the inbred '81 B' in 50 seeds or the line 'ICMB 90111'), indicating its potential for testing the genetic purity orpearl millet seed lots.